Digital practices across the UK population: The influence of socio-economic and techno-social variables in the use of the Internet. (June 2022) - Calderón Gómez, Daniel; Ragnedda, Massimo; Laura Ruiu, Maria
This article investigates the entanglement between socio-economic and technological factors in conditioning people's patterns of Internet use. We analysed the influence of sociodemographic and techno-social aspects in conditioning the distinctive digital practices developed by Internet users. By using a representative sample of UK users and different methods of analysis, such as factor analysis, K-means cluster analysis and logit analysis, this study shows how techno-social variables have a stronger effect than socio-economic variables in explaining the advanced use of the Internet.